(untitled) (Scientiae Studia, 2016)
The goal of this article is to lay some foundational groundwork in the study of epistemic representations in general, and visual epistemic representations in particular. To this goal, I introduce three helpful and closely related distinctions: The first one is a distinction between the constraints imposed on a tool by the task it is intended to help perform, and the constraints imposed by its intended user. The second is a distinction between a representation’s narrow representational function (to represent something), and its wider purpose, which could be epistemic, aesthetic etc. Finally, the third one is a distinction between interpreting and applying a representation, that is, between determining how things are according to the representation, and determining whether things actually are as they are represented to be. I illustrate the usefulness of these distinctions by applying them to a couple of examples: a case of photo finish and a diagram of Euclidean Geometry